Influence of Woven Filament Geotextile Additative in Modification of Clay Soils - K.Peeraiah, Dr.V.Ramesh Babu, K.Niveditha (International Journal of Advanced Science and Technology, 2020)
The expansive soil problems more on to the  structural and geotechnical engineering challenges all over the world. Expansive soils are the different types of soils, which their volume changes considerably depend on their water content.When expansive soils obtain moisture,they expand or swell up.Likewise,when expansive soils lose moisture they begin to shrink.Expansive soils covers many areas in the world,especially the arid and semi arid regions.There are several areas exists  in Sudan for this expansive(problematic) soil. This paper is a comprehensive study on expansive soils,its nature,shrinkage-swell behaviour,as well as expansive soil causes and treatments.Geotextile have been successfully used for reinforcement of soils to improve the performance of bearing capacity of weak reinforced soil  and  with reinforced earth technique is a very effective ground improve technique because of its cost effectiveness,easy adaptability and reproducibility and workability etc.In this project reportwork,order to investigate the behavior of geosynthetic-reinforced soil(GRS),a series of  laboratory experiments were conducted on GRS samples made up of four different types of expansive soils reinforced with a Woven Filament  Geotextile(WFG).The California Bearing Ratio(CBR) and unconfined compressive strength(UCS) of the GRS mass were the parameters examined to evaluate the performance of the GRS four samples.Soil reinforced with randomly distributed discrete Woven Filament Geotextile(WFG) at different aspects ratios of layers of 0,1,2,3.The focus of the tests was to study the effects of the vertical spacing of the reinforcement and the relative compaction of the granular soil on the performance of the GRS mass.Further more than the well-compacted granular soil reinforced with closely spaced geotextile not only has a higher compressive strength compared to that with widely spaced reinforcement,but also exhibits both ductile and flexible failure mode making it a desirable composite material for the construction of supporting structures.